Playing games, receiving gifts, creating experiences and building brands. Issue 4 (6th June 2016) - Pratap, Sankalp; Gupta, Agam; Mateen, Arqum; Mahto, Kavita
Abstract : Purpose: – The purpose of this paper is to extend the understanding the role of consumer experiences, instantiated through gift giving and game play, in communication of brand values. Design/methodology/approach: – The paper is based on in-depth phenomenological interviews of marketing managers and various channel intermediaries involved in the execution of a mass brand promotion program in rural India. Findings: – The study reveals the employment of innovative game designs and gift choices, their design rooted deep in the village populace's context and life experiences. It shows how the consumer's experience created through games and gifts shapes their perceptions about the brand leading to favorable consideration and purchase outcomes for it. Research limitations/implications: – This work is derived primarily from practice. It is hoped that industry practitioners will benefit from this stream of research and will use games and gifts in innovative ways to engage customers and create brand experiences. Originality/value: – This is one of the first works to highlight the importance of games and gifts in experiential marketing literature. It brings into focus one of the largely unexplored facets of customer engagement in rural India.